Pyramid projection - validation of a new method of skin defect measurement - Růžička, Jiří; Nový, Pavel; Vávra, F; Bolek, Lukáš; Beneš, Jiří (Physiological research, 2007)
This paper presents a new method for the determination of the volume, surface area and depth of skin defects. The method is based on the description of a spatial defect using a pyramid (made, for example, from injection needles), which is placed over the defect. The projection of the pyramid on to the defect is photographed using a digital camera and subsequently compared with the projection of the same pyramid on to a sheet of grid paper. The defect is mathematically reconstructed on a computer, and an optimal body shape describing the defect is found, using a number of simplifications and assumptions. The method was then validated using a plaster mold of a real foot with 19 defects simulating real wounds. These plaster wounds were molded using alginate hydrocolloid, and the volume, surface area and depth were measured and compared with the results of the pyramid projection by means of regression analysis.This method correlates in all variables with correlation coefficients higher than 0.9. It can be concluded that the projection pyramid method correlates well with the reference mold method and can be used with good results for a whole range of variables.
Keywords: Photography; reprodukovatelnost výsledků; Signal Processing, Computer-Assisted; Wounds and Injuries; počítačové zpracování signálu; fotografování; zobrazování trojrozměrné; lidé; software; Imaging, Three-Dimensional; Reproducibility of Results; Software; Humans; kůže; Foot Ulcer; vředy na noze (od hlezna dolů); Skin; rány a poranění